Study of Hadith Takhrij in the 2013 Curriculum MI Al-Qur'an Hadith Book - Mubarak, Hafiz; Abqari, Salim; Rahmani, Muhammad Fadli (Proceedings of International Conference on Muslim Society and Thought, 2024)
The purpose of this study is to determine the existence and authentic source of the traditions contained in the 2013 curriculum MI Al-Qur'an Hadith book contained in the hadith master book along with its complete sanad and matan. This type of research is literature research using the descriptive-analytical method, which is to do takhrij hadith bil-lafzhi both at the beginning, middle, and end of the hadith text. The results of the takhrij study of the three traditions in the book are that the Hadith about honoring parents is not sourced from Bukhari, but sourced from At-Tirmidhi and the wording of the Hadith is also different, while the Hadith about cleanliness and the Hadith about good deeds are in accordance with the sources of transmission, but there are slight differences in wording